2022
DOI: 10.1021/acsami.1c19962
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Oxygenating Fluorinated Methacrylamide Chitosan Microparticles to Increase Cell Survival and Function in Large Liver Spheroids

Abstract: Despite advances in the development of complex culture technologies, the utility, survival, and function of large 3D cell aggregates, or spheroids, are impeded by mass transport limitations. The incorporation of engineered microparticles into these cell aggregates offers a promising approach to increase spheroid integrity through the creation of extracellular spaces to improve mass transport. In this study, we describe the formation of uniform oxygenating fluorinated methacrylamide chitosan (MACF) microparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…Additionally, due to the presence of oxygen-rich domains within MACF hydrogels, they can be seen as oxygen transport enhancers that are constantly reabsorbing and redissolving oxygen in the culture to benefit metabolically active cells, rather than simply serving as a limited reservoir for oxygen. 12,14 After the confirmation of successful oxygenation from MACF treatment, the study of the release profile of PHMB from MACF substrates was vital to understand the amount of antibiotic in contact with cells over time. Accordingly, the release kinetics of PHMB from the MACF substrates showed a burst phase profile during the first 30 h followed by a slowrelease phase (up to 51 h in Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, due to the presence of oxygen-rich domains within MACF hydrogels, they can be seen as oxygen transport enhancers that are constantly reabsorbing and redissolving oxygen in the culture to benefit metabolically active cells, rather than simply serving as a limited reservoir for oxygen. 12,14 After the confirmation of successful oxygenation from MACF treatment, the study of the release profile of PHMB from MACF substrates was vital to understand the amount of antibiotic in contact with cells over time. Accordingly, the release kinetics of PHMB from the MACF substrates showed a burst phase profile during the first 30 h followed by a slowrelease phase (up to 51 h in Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrated that our hydrogels are able to attract and dissolve molecular oxygen to enhance the local oxygen levels in aqueous buffered cell cultures, , which we again confirmed with our newest data (Figure, E). Additionally, due to the presence of oxygen-rich domains within MACF hydrogels, they can be seen as oxygen transport enhancers that are constantly reabsorbing and redissolving oxygen in the culture to benefit metabolically active cells, rather than simply serving as a limited reservoir for oxygen. , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To demonstrate the utility of the MFD culture platform, we generated large (4k cells/well) spheroid models from the Lymph Node Carcinoma of the Prostate (LNCaP) cell line. Large spheroids achieve better physiological relevance in terms of growth, cell function, and drug responses, but have been underutilized in in vitro studies due to challenges in viability and long-term growth [38, 39]. We investigate that LNCaP spheroids in the MFD exhibit reduced necrosis and hypoxic stress and maintain cellular structural integrity throughout the spheroid.…”
Section: Introductionmentioning
confidence: 99%